Analysis of Critical Thinking Ability of Middle School Students Based on Adversity Quotient in Algebra Material - Sugesti Rahayu; Arsuti Vizha (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2024)
This research aims to evaluate students' critical thinking abilities in class VII algebra material and focuses on their Advesity Quotient (AQ). Using a qualitative approach, class VII students of SMP Negeri 2 Sempu were used in research involving five students and each representing a different AQ category. This research uses the ARP questionnaire, critical thinking test questions, and interview guidelines to collect data. The findings show that students with high AQ show better critical thinking skills than students with low AQ. This difference is likely due to the influence of AQ on students' problem solving methods. This research is important because it identifies the correlation between AQ and students' critical thinking skills, so that teachers can improve students' critical thinking skills by increasing their AQ levels effectively.